2001
DOI: 10.1897/1551-5028(2001)020<2038:soecfe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Environmental Contaminants for Ecdysteroid Agonist and Antagonist Activity Using the Drosophila Melanogaster Bii Cell in Vitro Assay

Abstract: The B(II) bioassay was developed as a rapid and reliable tool for detecting potential insect growth regulators acting as ecdysteroid receptor (ant)agonists. Based on an ecdysteroid-responsive cell line from Drosophila melanogaster, this microplate assay is ideally suited to the evaluation of environmental contaminants as potential endocrine disrupters. Data are presented for about 80 potential environmental contaminants, including industrial chemicals, pesticides, pharmaceuticals, phytoestrogens, and vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 20 publications
(37 reference statements)
4
42
0
1
Order By: Relevance
“…Chemicals with antiecdysteroidal activity include many of the classic estrogen receptor agonists of vertebrate. However, studies with ecdysteroid-responsive insect cells have demonstrated that non-steroidal EcR agonists are rare [62]. The binding of an environmental chemical to the EcR will more likely result in inhibition of ecdysteroid signaling.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals with antiecdysteroidal activity include many of the classic estrogen receptor agonists of vertebrate. However, studies with ecdysteroid-responsive insect cells have demonstrated that non-steroidal EcR agonists are rare [62]. The binding of an environmental chemical to the EcR will more likely result in inhibition of ecdysteroid signaling.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 99%
“…Both of these chemicals may inhibit ecdysteroidsynthesis through this enzyme inhibition. The 4-Nonylphenol is an antagonist of the insect ecdysteroidreceptor in vitro [62]. Bisphenol A was proposed to elicit anti-ecdysteroidal activity through a receptor cross-talk mechanism [71,74].…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 99%
“…In the D. melanogaster BII cell line, BPA was shown to act as an ecdysteroid antagonist, but only at a high exposure concentration of 22.8 mg l 21 (Dinan et al 2001). Studies combining BPA with other chemicals have shown interactive effects, affecting the number of embryo abnormalities and offspring emergence (Mu et al 2005;Wang et al 2005).…”
mentioning
confidence: 99%
“…For example, male vertebrate sex steroid hormone testosterone (in relatively high concentrations 5-40 ”M) interfered with 20-HE signalling in Daphnia magna Straus, 1820 causing abnormal progeny development and prolongation of the first molting (Mu & LeBlanc 2002). Testosterone (Mu & LeBlanc 2002) as well as three estrogens, bisphenol A, diethylphtalate and lindane (Dinan et al (2001), antagonized effects of 20-HE in an insect (Drosophila) in vitro model systems indicating a ligand-competitive mechanism. Similarly, other two xeno-ecdysteroids, strong fytoecdysterone agonist Ponasterone A and synthetic ecdysone agonist bisacylhydrazine RG-102240, are potent lignads for EcR (that heterodimerizes with RXR) in U. pugilator (Wu et al 2004).…”
Section: Role Of Classical Endocrine Glands In Reproductionmentioning
confidence: 99%